Self-control and criminal opportunity - Longshore, Douglas (Criminal justice and behavior, 1998)
In this study, the authors tested two hypotheses drawn from the general theory of crime. The first hypothesis is that low self-control is a major individual-level cause of crime. The second, that the effect of self-control is contingent on criminal opportunity. The measure of self-control used was a 23-item self-report index. To measure criminal opportunity, two proxy variables were used: gender and crime-involved friends. Crime measures included number of criminal acts of force and number of criminal acts of fraud reported in a 6-month recall period by a sample of 522 criminal offenders. Self-control was lower among offenders reporting more crimes of force and fraud, but the variance explained by self-control was low in each case. The relationship between self-control and fraud crimes was contingent on criminal opportunity, but the relationship between self-control and force crimes was not. Implications of these findings for the general theory of crime are reviewed